Pembagian jaringan komputer menggunakan virtual local area network guna mendukung perpustakaan digital - Hero Wintolo; Amalia Farhati (Jurnal Kajian Informasi dan Perpustakaan, 2020)
Digital libraries have been widely applied in educational institutions in Indonesia as a complement conventional libraries. The purpose of this research is to know division computer network access at the Adisutjipto Intitute of Technology (STTA) library. The research method used is a qualitative method using Prepare Plan Design Implement Operate and Optimize (PPDIOO). The result research is that people who have internet access will not be able to enter the digital library network. Computer network users who want to access digital libraries must log into the computer network that provides digital books in the library using a Virtual Local Area Network (VLAN). Making this VLAN requires a computer network infrastructure in the form of a Local Area Network (LAN) and computer network equipment in the form of a switch that can be used to configure multiple VLANs in a LAN. Some of the existing services in the library are placed on one VLAN and the digital library is placed on another VLAN. From the test results, it can be seen that between computers that provide services in the library on VLAN 2 cannot communicate via the connecting network to VLAN 1 where the digital library with website based services will be located. This is evidenced by the ping command which generates request time out information. VLANs network in the STTA library have been able to provide support for plans to improve services to members and academicians in the form of a digital library.